Ferrari [videorecording (Blu-Ray)] - Martin, Troy Kennedy, 1932-2009; Driver, Adam; Cruz, Penélope; Woodley, Shailene; Gadon, Sarah, 1987-; Leone, Gabriel; O'Connell, Jack, 1990-; Dempsey, Patrick, 1966-; Yates, Brock, 1933-2016 (Decal Releasing, 2024)
During the summer of 1957, bankruptcy looms over the company that Enzo Ferrari and his wife built 10 years earlier. He decides to roll the dice and wager it all on the iconic Mille Miglia, a treacherous 1,000-mile race across Italy.